Gaps in expectations of a cotton producer: the case of Rwenzori cotton farmers in Uganda. (1st June 2021) - Abainenamar, Yorokamu K.
Abstract : The plight of the smallholder cotton farmer in the Rwenzori region of western Uganda starts with the unfair terms of hiring land for cultivation. The next hurdle is the loss of ownership of the cotton at the earliest stage of the value chain after delivering the produce to the ginner. Even the Fairtrade standards base the minimum price for the farmer on delivery of seed cotton at the ginnery, implying that the farmer is not expected to participate in the value chain and share the accruing value additions further up the chain. However, members of the Rwenzori Farmers' marketing Co-operative Society decided to move a step up the value chain by hiring the ginning services and, hence, retained the ownership of both the lint and cotton seed, which improved their income by at least 30 per cent. The strategy is to find investors to enable them to spin the cotton and manufacture the final products.